Ultrasonic fatigue of superelastic Nitinol and in situ synchrotron observation of strain and damage - M. Fitzka; H. Rennhofer; D. Catoor; M. Reiterer; S. Checchia; M. di Michiel; H.C. Lichtenegger; H. Mayer (Journal of Materials Research and Technology)
Superelastic Nitinol was tested at ultrasonic frequency in the high and very high cycle fatigue regime. Thin sheet specimens were initially preloaded to mimic crimping and deployment of Nitinol implants, which lead to a sample in a multi-phase state with martensitic phase in the middle and adjacent zones with austenitic phase. In situ synchrotron X-ray diffraction (XRD) was used to monitor cyclic strains over an entire ultrasonic cycle, and to compare the results with low frequency loading. Both austenitic and martensitic regimes showed similar sinusoidal elastic deformation at cycling frequencies 0.1 Hz and 18.3 kHz, and strains were comparable over the entire gauge section of the specimen. XRD data showed progressive growth of austenitic bands in formerly martensitic areas with increasing numbers of ultrasonic cycles. This increased specimen stiffness and cyclic stresses promoting crack initiation, which nearly exclusively occurred at cracked surface inclusions. The strain versus fatigue lifetime diagram shows a pronounced change in slope below 106 cycles. The overlapping properties measured at low and ultrasonic frequency demonstrate that ultrasonic fatigue testing is in principle appropriate for rapid characterization of the cyclic properties of Nitinol.